Sidestep Training Model of a Rugby Game - Aris Triyanto; Fahmy Fachrezzy; Iman Sulaiman; Oman Unju Subandi (Universitas PGRI Palembang, 2023)
This study aims to produce a sidestep training model by testing the effectiveness of sidestep enhancement in rugby athletes. This research uses research and development methods from Borg and Gall. The subjects of this study were athletes from the Jakarta State University Rugby club and the Sumedang City Rugby club. The research begins with needs data analysis, planning, product manufacturing, testing, revision and final product. The feasibility test of the model presented 3 experts consisting of 3 National rugby coaches and produced 20 sidestep training models. The effectiveness test model uses sidestep results. The improvement in shooting skills showed significant t-count= 15,138, df= 29 and p-value= 0.00<0.05 which means that there is a significant difference between before and after being given the training model treatment, the average pre-test is smaller than the average post-test of. It can be concluded that the developed sidestep training model of rugby games is quite effective for improving sidestep skills in rugby athletes.